The quest for press freedom : one hundred years of history of the media in Ethiopia - Reta, Meseret Chekol (University Press of America, 2013)
This book is about press development and freedom in Ethiopia, with a focus on the state media. It examines the political and social situations of the monarchy era, the Marxist military regime, and the current ethnic federalist regime, and analyzes the effects they had on the media.